Províncias gemológicas do Vale do Jequitinhonha: geodiversidade e potencial geoturístico a partir das identidades garimpeiras - Liliane Rodrigues de Oliveira Braga (2021)
In recent decades, studies on geodiversity and the relevance of the conservation of its associated geoheritage have been recurrent in the national and international context. The gemological diversity present in the Jequitinhonha Valley, located in the northeastern portion of Minas Gerais, added to its historical and cultural events, has given this region a rich cultural heritage, originating from a unique composition, which encompasses indigenous, African, and Portuguese influences. In this perspective, this "Valley of Culture" holds important testimonies of the history of diamond, tourmaline, and marine water mining, expressed in its built heritage and in its landscapes, as well as various cultural manifestations, such as festive territorialities, musical expressions, handicraft, gastronomy, literature, festivals, which make up the identity of its remaining mining communities. In this perspective, the objective of this study was to identify the cultural values of geodiversity associated with the Jequitinhonha Valley gemstones and demonstrate the potential of this region for the development of geotourism. The methodological procedures adopted included: qualiquantitative research, with bibliographic research; field surveys; systematization and analysis of data and critical reflection on the information collected. The qualitative research included ethnographic methods and the quantitative research consisted of the inventory and quantification of the identified sites identified in the study from the perspective of the remaining communities of prospectors and their descendants. The results show that the Jequitinhonha Valley, in the upper, middle, and lower reaches of the river, offers important elements linked to the cultural values of geodiversity, which portray a strong regional identity, and has sites linked to geodiversity and the history of diamond mining, tourmalines, and aquamarine, classified as high and medium potential for the practice of geotouristic activities. The speeches of the investigated interlocutors indicate that the cultural heritage of the studied areas is configured as a representative trait of the regional identity, demanding the adoption of valorization actions by the government and other entities so that their traditions are maintained.